Analysis of the nutritional status in the Palestinian territory: a review study - A. Assaf, Enas; Al Sabbah, Haleama; Al-Jawadleh, Ayoub (Frontiers in Nutrition, 2023)
Background Food insecurity, occupation, and poverty contribute to the poor nutritional status of Palestine. This review study aimed to analyze the nutritional status in the Palestinian Territory by analyzing published data from 2011 to 2023. Method Searching for relevant publications yielded 67 studies. Based on reviewing these studies, five major themes were identified: low birth weight, breastfeeding, obesity and overweight, protein-energy malnutrition, and micronutrient deficiency. Results Based on the review of these studies, five major themes were identified, namely, low birth weight, breastfeeding, obesity and overweight, protein-energy malnutrition, and micronutrient deficiency. Based on the literature, the prevalence rate of exclusive breastfeeding was 24.4% in the Gaza Strip, compared to a national rate of 39.9% in 2020. Smoking, anemia in mothers, diet during pregnancy, and indoor pollution were associated with low birth weight. One-fifth of the boys and girls were stunted by 2 years of age in the Gaza Strip, and girls were more stunted than boys. The prevalence rates of underweight, overweight, and obesity among school children in the West Bank were 7.3%, 14.5%, and 15.7%, respectively. Age, gender, and living area were significant predictors of being overweight among school children. The prevalence rates of overweight and obesity among adults in Palestine were 57.8% and 26.8%, respectively. Obesity is associated with a family history, chronic diseases, and low physical activity among adults. Exclusive breastfeeding was below the WHO recommendations, while significant rates of obesity and overweight were found among children and adults. Iron-deficiency anemia (IDA) among pregnant women and children remains a challenging public health issue, while other micronutrient deficiencies are high among children. Conclusion This review emphasizes the need for multi-sectoral interventions to address malnutrition and nutritional shifts. It identifies gaps and addresses nutrition-related issues in the Palestinian Territory, which can serve as a basis for guiding United Nations agencies and governments in formulating evidence-based policies and strategies for prioritizing nutritional interventions to meet sustainable development goals.